2007
DOI: 10.3168/jds.2006-624
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Addition of Milk Replacer to Colostrum Whey: Effect on Immunoglobulin G Passive Transfer in Majorera Kids

Abstract: Forty-two Majorera kids (21 males and 21 females) were assigned to 3 groups, a colostrum group (C), a colostrum whey group (CW), and a colostrum whey plus milk replacer group (CWMR). All kids were fed twice on the first day and received 4 g of IgG/kg of body weight. No differences were found in serum IgG among the different treatments. Kid serum IgG concentrations on d 2 were 14.57, 17.25, and 13.32 mg/mL in the C, CW, and CWMR group, respectively. Labor time per animal was higher in the C and CW treatments th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…Thus, IgG absorption was related to apoptotic changes in enterocytes. Serum blood IgG was not recorded in the present experiment, but previous experiments (Castro et al, 2005(Castro et al, , 2007 demonstrated that the main period for IgG absorption in kid goats was the first 24 h of life. On d 2 of life, the cytoplasm and vascular villi of some enterocytes displayed marked IgG immunostaining (Figure 1; arrow in IgG on d 2).…”
contrasting
confidence: 64%
“…Thus, IgG absorption was related to apoptotic changes in enterocytes. Serum blood IgG was not recorded in the present experiment, but previous experiments (Castro et al, 2005(Castro et al, , 2007 demonstrated that the main period for IgG absorption in kid goats was the first 24 h of life. On d 2 of life, the cytoplasm and vascular villi of some enterocytes displayed marked IgG immunostaining (Figure 1; arrow in IgG on d 2).…”
contrasting
confidence: 64%
“…In order to ensure the survival of lambs, each animal (from both groups) was also fed at 24 h after birth. The total volume of colostrum was equivalent to 4 g of IgG/kg of BW as previously suggested in colostrum immune studies [26,63]. …”
Section: Methodsmentioning
confidence: 99%
“…After the initial increase in IgG serum concentrations between birth and d 1, there was a slight decrease in both experimental groups. Argüello et al (2004), Castro et al (2007), and Rodríguez et al (2009) reported similar blood serum peak times for IgG concentrations in Majorera kids. This temporal change in IgG concentration is in accordance with observations made by Logan et al (1978) in calves, where the maximum IgG level was reached between 16 and 48 h postpartum.…”
Section: Resultsmentioning
confidence: 74%